الحلول الوقائية للحد من ظاهرة الطلاق في ضوء القرآن الكريم = Preventive measures to reduce the phenomenon of divorce in the light of the Quran - Alharby, Seddiq; Elatrash, Radwan Jamal Yousef (IIUM Press, International Islamic University Malaysia, 2020)
على الرغم من أن أحكام الشريعة الإسلامية المتعلقة بالأسرة اتسمت بالشمولية، والخير والعدالة والمساواة والهداية للبشرية ،ولها سمة الخلود والصلاحية والرحمة والمرونة إلا أ ن المراقب يجد أن نسبة الطلاق في الأسر المسلمة ارتفعت إلى حد لا يستهان به، بل هي م رعبة إن جاز لنا التعبير، فمنها ما يتعلق بالأسلوب التربوي بالأولاد ،ومنها إجبار المرأة العاملة على الإنفاق على البيت، كما أن لوسائل التواصل الاجتماعي دو ر ا عظيم ا في إحداث هذا الشرح الاجتماعي الصعب والشقاق الجارح وتسريع عجلة الطلاق ،وكل ذلك ي رجع إلى عدم تقوى الله عز وجل من الطرفين. والبحث التزم بالمنهج الاستقرائي والتحليلي لل وصول إلى بعض الحلول الوقائية للحد من ظاهرة الطلاق في ضوء القرآن الكريم .وقد ت وصل البحث إلى أن أهم الأسباب التي تؤدي إلى الطلاق هي: قلة الصبر والغضب الشديد والمصاريف الباهظة وقطع الأ رحام. كما أن القرآن الكريم قدم لنا حلولا عظيمة لل وقاية من الطلاق منها: اختيار ذات الدين لتكون أم الأولاد، ثم التحلي بالقناعة والحلال والشفافية في التعامل مع الطرف الآخر وال رضا بالقليل والتحلي بالصبر وغير ذلك. ********************************************************************************* Although the ordinances of Islamic law related to the family were characterized by inclusiveness, goodness, justice, equality and guidance to mankind, and has the character of immortality, validity, mercy and flexibility, but the observer finds that the rate of divorce in Muslim families has risen to a considerable extent, but is terrifying if we may speak. Some of them related to the pedagogical method of children, including forcing working women to spend on the home not to forget Social media which has a great role to play in accelerating divorce. The research adhered to the inductive and analytical approach to reach some preventive solutions to reduce the phenomenon of divorce in the light of the Holy Quran. The research found that the most important reasons that lead to divorce are: lack of patience, extreme anger, Excessive expenses and cutting the relations of the womb and violating relations between family kinship. One of the solutions provided by the Koran to stop the phenomenon of divorce: Choose a good wife, contentment, and patience.